Simulation and Experiment of Rising-Sun Resonant Structures Fabricated for X and Ku Ranges Magnetrons with Two Outputs of Energy - Gennadiy Churyumov; Shuang Qiu; Nan-nan Wang; Wei Li; Volodymyr Gerasimov; Tetyana Frolova (New Trends in Physical Science Research Vol. 6, 2022)
The azimuthal distributions of a longitudinal electric component of the RF field for either of the excited modes are shown in this study, as well as the simulation results of the oscillation modes excited in the interaction spaces of anode blocks of X and Ku ranges magnetrons. Anode blocks with distinct resonator configurations were investigated using CST code: a rising sun anode block and a rising sun hole-and-slot anode block. For varied geometrics of their cavities, the dispersion properties and distributions of the azimuthal components of the RF field are described as applicable to the X and Ku ranges. The condition of acceptable separation both in frequency and in phase velocity between the operating N/(2 ) - mode (or \(π\) -mode) and neighboring (N/(2 -1)) - mode has been determined. It is proposed that the mechanism for producing the total RF field is linked to the probable interference of several RF fields created in a resonant system with small and large cavities. The operation features of the magnetrons with two outputs of energy are presented. The experimental characteristics of the given magnetrons are given. The results of the simulation are in good agreement with the experiment.